Airway Closure and Expiratory Flow Limitation in Acute Respiratory Distress Syndrome - Guérin, Claude; Cour, Martin; Argaud, Laurent (Frontiers in Physiology, 2022)
Acute respiratory distress syndrome (ARDS) is mostly characterized by the loss of aerated lung volume associated with an increase in lung tissue and intense and complex lung inflammation. ARDS has long been associated with the histological pattern of diffuse alveolar damage (DAD). However, DAD is not the unique pathological figure in ARDS and it can also be observed in settings other than ARDS. In the coronavirus disease 2019 (COVID-19) related ARDS, the impairment of lung microvasculature has been pointed out. The airways, and of notice the small peripheral airways, may contribute to the loss of aeration observed in ARDS. High-resolution lung imaging techniques found that in specific experimental conditions small airway closure was a reality. Furthermore, low-volume ventilator-induced lung injury, also called as atelectrauma, should involve the airways. Atelectrauma is one of the basic tenet subtending the use of positive end-expiratory pressure (PEEP) set at the ventilator in ARDS. Recent data revisited the role of airways in humans with ARDS and provided findings consistent with the expiratory flow limitation and airway closure in a substantial number of patients with ARDS. We discussed the pattern of airway opening pressure disclosed in the inspiratory volume-pressure curves in COVID-19 and in non-COVID-19 related ARDS. In addition, we discussed the functional interplay between airway opening pressure and expiratory flow limitation displayed in the flow-volume curves. We discussed the individualization of the PEEP setting based on these findings.